Tau-PET imaging in Parkinson's disease: a systematic review and meta-analysis - Zhang, Junjiao; Jin, Jianing; Su, Dongning; Feng, Tao; Zhao, Huiqing (Frontiers in Neurology, 2023)
Background Pathological tau accumulates in the cerebral cortex of Parkinson's disease (PD), resulting in cognitive deterioration. Positron emission tomography (PET) can be used for in vivo imaging of tau protein. Therefore, we conducted a systematic review and meta-analysis of tau protein burden in PD cognitive impairment (PDCI), PD dementia (PDD), and other neurodegenerative diseases and explored the potential of the tau PET tracer as a biomarker for the diagnosis of PDCI. Methods PubMed, Embase, the Cochrane Library, and Web of Science databases were systematically searched for studies published till 1 June 2022 that used PET imaging to detect tau burden in the brains of PD patients. Standardized mean differences (SMDs) of tau tracer uptake were calculated using random effects models. Subgroup analysis based on the type of tau tracers, meta-regression, and sensitivity analysis was conducted. Results A total of 15 eligible studies were included in the meta-analysis. PDCI patients (n = 109) had a significantly higher tau tracer uptake in the inferior temporal lobe than healthy controls (HCs) (n = 237) and had a higher tau tracer uptake in the entorhinal region than PD with normal cognition (PDNC) patients (n = 61). Compared with progressive supranuclear palsy (PSP) patients (n = 215), PD patients (n = 178) had decreased tau tracer uptake in the midbrain, subthalamic nucleus, globus pallidus, cerebellar deep white matter, thalamus, striatum, substantia nigra, dentate nucleus, red nucleus, putamen, and frontal lobe. Tau tracer uptake values of PD patients (n = 178) were lower than those of patients with Alzheimer's disease (AD) (n = 122) in the frontal lobe and occipital lobe and lower than those in patients with dementia with Lewy bodies (DLB) (n = 55) in the occipital lobe and infratemporal lobe. Conclusion In vivo imaging studies with PET could reveal region-specific binding patterns of the tau tracer in PD patients and help in the differential diagnosis of PD from other neurodegenerative diseases. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/.